Davidson and the idiolectic view - Gumm, Derek, author; Losonsky, Michael, advisor; Kneller, Jane, committee member; Chong, Edwin, committee member (Colorado State University. Libraries, 2013)
In this thesis, I defend and expand Donald Davidson's view of language and linguistic meaning. I begin by looking at two positions that appreciate the sociality of language and linguistic meaning in two different ways. One view, as exemplified by Michael Dummett, sees the meaning of words as a feature of a language that holds independently of any particular speaker, while the other view, as exemplified by Davidson, sees meaning as depending on particular speakers and interpreters, their intentions, and their interactions. I find a serious tension in the former view and side with the latter, which I dub the idiolectic view of language. In the second chapter, I analyze Davidson's claim that understanding gives life to meaning. Using this analysis as a jumping off point, I outline the primary features of the Davidsonian idiolectic program. Finally, I conclude that the idiolectic features of this position place a special emphasis on the moment at which two people's personal understanding of language overlap and that such an emphasis is best understood in terms of events as particulars. In the third and final chapter, I argue that an ontology that countenances events as particulars is required for the idiolectic view of interpretation to get off the ground. First, I outline some of Davidson's classic arguments in favor of an ontology of events for action sentences and expand them to the case of what I call second-order language sentences, sentences about communication. Next, I discuss the importance of a criterion of event identity and individuation, working from some of Davidson's own arguments. I then extend Davidson's analysis of action sentences to second-order language sentences in order to determine the essential features of the linguistic event-type. Finally, I conclude that some basic notion of a language is required by this idiolectic view despite what Davidson originally thought. However, it is not the notion of a shared language that Dummett originally had in mind.
Keywords: Davidson; idiolect; Dummett